1996
DOI: 10.1143/ptp.95.1121
|View full text |Cite
|
Sign up to set email alerts
|

Two-Octupole-Phonon States in 146,148Gd

Abstract: 1121The so-called "two-octupole-phonon states" in 146. 148 Gd are theoretically analyzed by using the Dyson boson mapping method. In our analyses, the free ground state of 146Gd is treated as doubly closed shell since Z=64 is rather good subshell closure. The starting collective multi-phonon space that we take consists of collective octupole phonons and collective monopole pairing phonons for 146Gd. Additionally correlated particle-pair modes with J ' *' 0 are included in the multi-phonon space for 148Gd. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In addition we have applied the Hermitian treatment to other various calculations for realistic cases. 16), 17), 9), 10) In all these works, we have checked the validity of the approximation of the Hermitian treatment by comparing it with the direct treatment, and all the results have shown that the Hermitian treatment gives deviations less than 1% from the direct treatment on the average, or ≤ 2% ∼ 3% even in the worst case. This implies that the Hermitian treatment is a surprisingly good approximation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition we have applied the Hermitian treatment to other various calculations for realistic cases. 16), 17), 9), 10) In all these works, we have checked the validity of the approximation of the Hermitian treatment by comparing it with the direct treatment, and all the results have shown that the Hermitian treatment gives deviations less than 1% from the direct treatment on the average, or ≤ 2% ∼ 3% even in the worst case. This implies that the Hermitian treatment is a surprisingly good approximation.…”
Section: Discussionmentioning
confidence: 99%
“…Hermitian treatment to other various calculations for realistic cases. 43), 44), 23), 24) In all these works, we have checked the validity of the approximation of the Hermitian treatment by comparing it with the direct treatment, and all the results have shown that the Hermitian treatment gives deviations less than 1% from the direct treatment on the average, or ≤ 2% ∼ 3% even in the worst case. This implies that the Hermitian treatment is a surprisingly good approximation.…”
Section: Hermitian Treatment Of the Boson Mapping For Collective Fermmentioning
confidence: 99%
“…20) Thus the D-type mapping for the collective subspace was finally established and has successfully been applied to various realistic nuclei. 10), 21) - 24) One of the main purposes of this paper is to represent the full detail of the D-type non-unitary boson mapping for the multi-collective-phonon subspace. The general theory of boson mapping is represented in §2.…”
Section: §1 Introductionmentioning
confidence: 99%
“…Then how can we explain the fact that it is a good approximation to the exact treatment in some realistic cases as was shown numerically in Refs. [29] and [30]? In this subsection, we show that the result of the Hermitian treatment is approximately valid in spite of the breakdown of the basic assumption.…”
Section: Approximation In the Conventional Treatmentmentioning
confidence: 99%
“…If this formula works well, we no longer need to solve the right and left eigenvalue problems so that the efforts of the numerical calculation is greatly reduced and besides we can take the advantage of the finiteness of expansion. With the help of the Hermitian treatment, D-type BET has been applied to many nuclei in the various range of the nuclear chart [23]- [30].…”
Section: §1 Introductionmentioning
confidence: 99%